Correlates of music training: Plasticity or predispositions? - Correia, Ana Isabel Costa (2024)
The possibility that music training improves cognitive and socioemotional abilities has captured the attention of researchers, the media, and the general population. Nevertheless, the inconsistency of the results and the theoretical and methodological limitations of the studies raise interpretative issues. Recent studies suggest that genetics might influence musical practice, aptitude, and achievements, as well as associations between musical and nonmusical domains. Although musical ability is often assumed to result from music training, it is not exclusive to musicians and varies widely among the general population, but the correlates of individual differences in musical abilities remain poorly understood. Through a series of five studies, this thesis investigated individual differences in musical ability among musically trained and untrained individuals. It examined how these differences relate to variables that are usually studied in the context of music training, namely cognitive ability, emotion recognition, personality, and sociodemographic variables. In Study 1, the ability to recognize vocal emotions was only weakly associated with music training, but strongly associated with music-perception abilities regardless of music training. In Study 2, the Musical Ear Test proved to be a reliable and valid method to assess musical ability online. In Study 3, professional musicians showed enhanced musical ability and different personality profiles compared to other individuals, but they were average in terms of cognitive ability. In Study 4, musical abilities were associated with cognitive ability and informal musical experiences but not with personality traits. Moreover, musically untrained individuals with enhanced musical aptitude performed similarly to trained individuals in cognitive ability, but lower in the personality trait openness-toexperience. In Study 5, participants provided relatively accurate ratings of their own musical ability, even though they tended to over-estimate their ability, a tendency that was exaggerated for men and for individuals with lower cognitive ability. Overall, the present research underscores the importance of considering the musicality of untrained individuals and differences among trained individuals to improve our understanding of associations between musical expertise and nonmusical abilities.